Proliferation and transmission patterns of Pasteurella multocida B:2 in goats - Shamsuddin, Mohd Shafarin; Saad, Mohd Zamri; Bejo, Siti Khairani; Saharee, Abdul Aziz (Springer Science + Business Media B.V. 2007, 2007)
This report describes the proliferation and transmission patterns of Pasteurella multocida B:2 among stressful goats, created through dexamethasone injections. Thirty seven clinically healthy adult goats were divided into three groups consisted of 15 goats in group A, 11 goats in group B and the remaining 11 in group C. At the start of the study, all goats of group A were exposed intranasally to 1.97× 1010 CFU/ml of live P. multocida B:2. Dexamethasone was immediately administered intramuscularly for 3 consecutive days at a dosage rate of 1 mg/kg. The exposed goats were observed for signs of HS for a period of 1 month. At the end of the 1-month period, 11 goats from group B were introduced into and commingled with the surviving goats of group A before all goats from both groups were immediately injected intramuscularly with dexamethasone for 3 consecutive days. The treatment with dexamethasone was then carried out at monthly interval throughout the 3-month study period. Goats of group C were kept separately as negative control. Three surviving goats from each group were killed at 2-week interval for a complete post-mortem examination. Two (13%) goats of group Awere killed within 24 hours after intranasal exposure to P. multocida B:2 while another two (13%) goats from the same group were killed on day 40, approximately 10 days after the second dexamethasone injection. All four goats showed signs and lesions typical of haemorrhagic septicaemia. Bacteraemia was detected in 3 goats of group A that were having rectal temperature higher than 41°C. The P. multocida B:2 isolation pattern was closely associated with dexamethasone injections when significantly (p<0.05) higher rate of isolations from both groups were observed after each dexamethasone injection. Transmission of P. multocida B:2 from goats of group A to group B was successful when P. multocida B:2 was isolated from goats of group B for a period of 28 days. There was a strong correlation between dexamethasone injections, rate of bacterial isolation and serum cortisol level. The IgG level showed an increasing trend 2 weeks after exposure to P. multocida B:2 and remained high throughout the study period.